Duplex Ultrasound Assessment of Native Stenoses in the Superficial Femoral and Popliteal Arteries: A Comparative Study Examining the Influence of Multisegment Lesions. (April 2015) - Macharzina, Roland Richard; Schmid, Simon F.; Beschorner, Ulrich; Noory, Elias; Rastan, Aljoscha; Vach, Werner; Schwarzwälder, Uwe; Sixt, Sebastian; Bürgelin, Karlheinz; Neumann, Franz-Josef; Zeller, Thomas
Purpose: To evaluate duplex ultrasonography (DUS) in the assessment of femoropopliteal stenoses comparing a single native stenosis (SNS) to multisegmental native stenoses (MNS).Methods: Among the 1284 patients treated for atherosclerotic occlusive disease involving the femoropopliteal segment between November 2002 and November 2012, 139 patients (97 men; mean age 68±8 years) with 142 SNS or 143 MNS in 79 and 60 patients, respectively, were eligible for this retrospective analysis. The peak systolic velocity ratios with proximal (PSVRprox ) and distal (PSVRdist ) reference for the 285 lesions were compared with their respective angiographic stenosis grade as measured by 2 independent readers using quantitative vascular analysis to ensure objectivity. Receiver operating characteristic curve analysis was used to evaluate sensitivity, specificity, and the optimal thresholds of PSV and PSVR for detection of stenoses by grade (>50%, >70%, or >80% diameter stenosis). The area under the curve (AUC) values of dependent and independent receiver operating characteristic curves were compared.Results: For SNS, correlation of PSVRprox to diameter stenosis (R=0.88) was higher (p<0.001) than the correlation for MNS (R=0.78). In the SNS group, the AUC for detecting a >50% (0.99±0.01), >70% (0.98±0.01), and >80% (0.96±0.01) stenosis with PSVRprox was significantly higher than in the MNS group [AUC50% 0.93±0.02 (p=0.01), AUC70% 0.92±0.02 (p=0.02), and AUC80% 0.87±0.03 (p=0.003)]. The optimal thresholds for detecting >50%, >70%, and >80% stenoses for SNS using PSVRprox were 2.6, 3.3, and 3.9, respectively. For MNS, the optimal thresholds of PSVRprox were 2.6, 3.4, and 3.9, respectively, with respective sensitivities of 87%, 81%, and 75%; respective specificities of 93%, 90%, and 82%; negative predictive values of 45%, 64%, and 74%; and positive predictive values of 99%, 95%, and 83%.Conclusion: DUS is an optimal tool for quantification of SNS. However, a multisegment setting has a significant negative impact on the quantification of femoropopliteal artery stenosis.